A visszatért Felvidék határának megállapítása : 1938-1939 - Suba, János (Közép-Európai Közlemények, 2011)
The borders set by § 1 of the Vienna Arbitration on 2nd November were drawn on a map of a 1 : 750 000 scale. Because of its small scale, this map did not indicate clearly where some smaller municipalities in the border region would belong. (The actual width of the line itself covered a 750m wide strip of land, crossing through hills and dells.) There was a committee set up to interpret and explain the new border line drawn by the Vienna Decision. It was called the Hungarian-Czechoslovakian Border Setting Committee. The committee’s task was to define the exact route of the border line and to define national belonging of the municipalities along it for the piece of land between the Danube and the River Ung. The Committee was in session from 3rd November 1938 to March 1939. Throughout its 25 sessions it made decisions about the border line’s detailed and precise route that were acceptable to both parties involved. The Hungarian-Slovakian border was set out in complete on 7th March 1939.